Depression among children at shelter care institutions in Terengganu Malaysia - Siti Hajar, Abdul Rauf; Asmah, Ismail; Nuratikah Azima, Razali (2020)
Background: Depression is a state of psychological disease that occurs to someone divers in age due to certain reasons. Among the factors include lack of self-confidence, problematic family, stress, low self-esteem and social environment. It could lead to a mental disorder that endangers the mental health. Aim: To investigate the status of children depression using the Children Depression Inventory (CDI) at 21 shelter care institutions in Terengganu Malaysia. Methodology: Quantitative research design was used. The sample consists of 404 respondents from 21 Islamic shelter cares such as Tahfiz, Madrasah and Orphanage in Terengganu Malaysia from the age of 10 to 18 years. Data was analyzed using Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) and Discriminant Analysis (DA) which then computed to identify the most dominant factors whereas reducing the initial five parameters with recommended >0.50 of factor loading. Results: Forward stepwise of DA shows the total of groups validation percentage by 92.08% (17 independent). The result showed that the highest frequency of respondent index was at a moderate level (62.87% respondents). This showed that children still can be controlled and cared to reduce depression.